Differential Effects of High-intensity Interval Training (HIIT) and Moderate-intensity Continuous Training (MICT) on Cardiac Follistatin-like 1 (FSTL-1) mRNA Expression in Wistar Rats - Nova Sylviana; Putri Karisa; Futri Wulan Agustin; Badai Bhatara Tiksnadi; Putri Teesa Radhiyanti Santoso; Hanna Goenawan (UPT Publikasi Ilmiah Universitas Islam Bandung, 2025)
Follistatin-like 1 (FSTL1) is a cardiokine that plays a protective role in cardiovascular health. Physical exercise, particularly aerobic training, has been shown to modulate FSTL1 expression. This study aims to compare the effects of high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) on mRNA expression of FSTL1 in the cardiac tissue of Wistar rats. This study employed an in vivo approach and was conducted at the Laboratory of Science, Universitas Padjadjaran, from December 2024 to May 2025. A total of 18 male Wistar rats were divided into three groups: control (no exercise, n=6), HIIT (n=6), and MICT (n=6), each undergoing an eight-week training protocol. Exercise was performed on a treadmill five times per week. Left ventricular heart muscle samples were collected for mRNA expression analysis of FSTL1 using real-time PCR. Data analysis was performed using one-way ANOVA followed by a post-hoc test. The results showed a significant difference in FSTL-1 expression among the three groups: control, MICT, and HIIT (p<0.05). Post-hoc tests revealed a substantial difference between the control and HIIT (p<0.05) and control and MICT (p<0.005) groups, but no significant difference was found between the MICT and HIIT groups (p>0.05). The absence of significant change in the MICT group compared to HIIT highlights the potential of HIIT as a more potent stimulus for cardioprotective gene expression. Further studies are needed to elucidate the underlying mechanisms and long-term effects. In conclusion, HIIT and MICT can upregulate cardiac FSTL-1 mRNA expression of Wistar rats.